Shuttling single metal atom into and out of a metal nanoparticle - Shuxin Wang (Nature Portfolio, 2017)
Doping a metal nanocluster with heteroatoms dramatically changes its properties, but it remains difficult to dope with single-atom control. Here, the authors devise a strategy to dope single atoms of Ag or Cu into hollow Au nanoclusters, creating precise alloy nanoparticles atom-by-atom.